DECENTRALIZATION, FISCAL CAPABILITY AND PUBLIC SPENDING EFFICIENCY - Abdul Hakim; Jaka Sriyana (Economic Journal of Emerging Markets, 2010)
Assigning autonomy to regency governments in Indonesia has failed to increase regency’s economies.While it increases regency government role in planning and initiating policies, its impact oneconomic development has been insignificant. This stems from the lack of institution’s capacity inorganizing the bulk funds transfer from the central government which leads to inefficiency in resourceallocation. This paper maps these regencies based on their fiscal dependency. This paperalso applies Data Envelopment Analysis to identify the efficient and non efficient regencies in sucha way that the non efficient regencies might use the efficient ones as the benchmark to increase theirefficiency.Keywords: Autonomy, regency government, efficiencyJEL classification numbers: H21, H53, H71, H72